The Influence of the Work Environment on Work Productivity of Land Acquisition Sub directorate Employees - Vanhoten, Renaldi; Hia, Ahmad Kultur; Partimah, Partimah; Fa’uzobihi, Fa’uzobihi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The main problem of the Subdirektorat Pengadaan Tanah is the non-physical work environment, such as work relationships between leaders and subordinates as well as work relations between fellow employees. This research aims to analyze the influence of the work environment on work productivity. The research method used is quantitative with an associative method to determine the relationship between environmental variables and productivity variables. In the t test, the value of t < t table is obtained (1.026 < 2.021). Regarding the partial correlation analysis, there is no influence of the work environment on work productivity, so Ho is accepted. From the results of the analysis, an R of 0.160 was obtained, which shows that there is no strong relationship between the environment and productivity. The results of the coefficient of determination show an R squared figure of 0.160 or 0.026%, which means that work environment variables influence work productivity by 0.026% while 0.074% is influenced by other factors not examined in this research. It can be concluded that there is no influence of the work environment on the work productivity of employees of the Subdirektorat Pengadaan Tanah.